Injustice at the Periphery: An Exploration of Corruption in Uche Nnyagu’s At the Centre of No-Man’s-Land (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Corruption and injustice are intertwined and pervasive issues that plague societies worldwide, perpetuating a cycle of oppression and undermining human dignity. Corruption, the abuse of power for personal gain, erodes trust in institutions and fosters an environment of impunity. Injustice, encompassing unfair treatment, discrimination, and inequality, further entrenches this cycle. The vicious cycle of corruption and injustice leads to political and economic instability, social and economic inequalities, erosion of trust in institutions, human rights violations, poverty and inequality in the society. This study explores how the novelist reflects corruption, injustice and oppression of the poor masses in a society where the common man is disregarded and exploitated by the various institutions and persons meant to safeguard his interests. This work shows a dysfunctional society and a government that has failed to protect the rights and liberty of its citizens. The African leaders abuse the powers of government but they are praised by their ignorant followers because of the crumbs they give to them. The post colonial criticism is adopted for the analysis of the text. The theory analyses the ideological forces that press the colonized to internalise the colonizers values and at the same time, promote the resistance of the colonized people against oppressors.
Keywords: Corruption; Injustice; Exploitation; Brutality; Post-Colonial